Institutionalizing Service Learning to Strengthen Community Engagement: A Case Study - Adarlo, Genejane (Archīum Ateneo, 2022)
Institutionalizing service learning as a community-embedded teaching practice requires changes within an organization. This case study aims to examine the reforms undertaken to institutionalize service learning in an institution of Catholic higher education based on Kotter’s theory of organizational change. Findings showed institutionalizing service learning is the response of the studied institution of Catholic higher education to the growing need to be true to its identity, mission, and core values: To foster student formation and to contribute to social development by strengthening its community engagement. Evidence also revealed internal acceptance, institutional readiness, and institutional commitment are key factors in institutionalizing service learning. This study can help leaders of similar institutions of higher education to recognize their patterns of adoption and resistance to strategic reforms so that they can make most of the short-term wins in institutionalizing service learning and anchor the use of this community-embedded teaching practice firmly in their institutional culture and infrastructure.